Growth of Hydrogenated Nano-crystalline Silicon (nc-Si:H) Films by Plasma Enhanced Chemical Vapor Deposition (PE-CVD). (March 2017) - Jadhavar, Ashok; Pawbake, Amit; Waykar, Ravindra; Jadkar, Vijaya; Kulkarni, Rupali; Bhorde, Ajinkya; Rondiya, Sachin; Funde, Adinath; Patil, Dinkar; Date, Abhijit; Pathan, Habib; Jadkar, Sandesh
Abstract: Hydrogenated nanocrystalline silicon (nc-Si:H) thin films were prepared by home-made PE-CVD systemfromgas mixture of pure SiH4 and H2 at various deposition pressures. Obtained results exhibited that deposition rate increases with increase in deposition pressure. Raman spectroscopy analysis revealed that deposition pressure in PE-CVD is a critical process parameter to induce nanocrystallization in Si:H films. The FTIR spectroscopy analysis results indicate that with increase in deposition pressure hydrogen bonding in films shifts from Si-H to Si-H2 and (Si-H2 )n bonded species bonded species. The bonded hydrogen content didn't show particular trend with optical band gap with change in deposition pressure. The obtained results indicates that 400 mTorr is an optimized deposition pressure of our PE-CVD unit to synthesize nc-Si:H films. At this optimized deposition pressure nc-Si:H films with crystallite size ∼ 5.43 nm having good degree of crystallinity (∼77%) and high band gap (ETauc ∼ 1.85 eV) were obtained with a low hydrogen content (4.28 at. %) at moderately high deposition rate (0.75 nm/s). The ease of the present work is to optimize deposition pressure to obtain device quality intrinsicnc-Si:H layer in view of its used in p-i-n solar cells.